An Investigation of Territory Concept in the Context of Two Residential Units in Ankara: Israel Houses and Saraçoğlu Neighborhood - Yavuz, Kadriye Burcu (ICONARCH International Congress of Architecture and Planning, 2014)
The term of territoriality has been a significant concept since the beginning of history for both animals and human being. It is required for the maintenance of their lives to sustain their nourishment, sheltering and the other needs. Accordingly, the reflection of this situation has shown itself as an occupancy desire. A special space which its boundaries are defined is needed to be occupied for that purposes by promoted by the archetype which is inside of us. In this sense, the space regulates the behavior of people depending on its hierarchical structure. As the hierarchy of the space changes, then the interaction between people also changes. To this respect, the term of space could be defined as a regulative mechanism which alters the connection among people. This is directly linked with the territoriality concept. The more personal the space, the less interaction between people. The less personal the space, the more interaction between people. The first type of the territoriality concept might cause introversion or alonessness. On the other hand, the second type of the territoriality concept might cause extraversion or socialness. Introversion / alonessness and extraversion / socialness are related with the privacy levels which are defined by the inhabitants of a specific territory. The relationship between the desired and achieved privacy levels constitutes the formation of introversion / alonessness or extraversion / socialness of the people in their boundaries of defined territories. In this context, territoriality concept is examined considering two residential areas in Ankara, named as Israel Houses residential unit and Saraçoğlu Neighborhood. The study is supported by field survey. In the process of field survey, the territorial boundaries in the residential areas have been recognized depending on their types. Whether the territory boundaries are defined or not is determined for the both residential area. Then, it is linked with the occupancy, privacy and archetype concepts. As a result of the field survey, it is observed that Israel Houses residential unit has exactly defined territory boundaries which constitutes an ideal situation for the interaction between people. However, it is confirmed that Saraçoğlu Neighborhood does not have exactly defined territory boundaries as in Israel Houses residential unit. Therefore, it could be stated that the interaction between people constitutes a level which might disturbs the inhabitants of the neighborhood which creates an unfavorable situation for them.